Environment-friendly waterproof and oil-proof emulsion with excellent washing durability function and preparation method of environment-friendly waterproof and oil-proof emulsion
By using two or more fluorine-containing monomers of different Tg or Tm in the waterproof and oil-proof emulsion, combined with specific copolymer design and ingredients, the problem that conventional short-chain fluorine-containing monomers cannot achieve the washing durability of C8 waterproof agents is solved, and excellent washing durability and environmental protection performance are achieved.
Patent Information
- Application Number
- CN202510157187.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-13
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2045-02-13
AI Technical Summary
The waterproof and oil-proofing agent of existing conventional short-chain fluorine-containing monomers cannot achieve the washing durability of C8 waterproofing agents.
Two or more fluorine-containing monomers with different Tg or Tm are used to prepare an environmentally friendly waterproof and oil-resistant emulsion with excellent washing durability through the design of fluorine-containing copolymers, combined with deionized water, emulsifier and cosolvent.
The washing durability comparable to that of C8 waterproofing agent is achieved, while avoiding C8 and above components with strong environmental accumulation in the environment, and improving the reconstitution resistance and softness of the polymer film.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of functional finishing agents for textiles, in particular to an environmentally friendly waterproof and oil-proof emulsion with excellent washing durability and a preparation method thereof. Background Art
[0002] As we all know, the mainstream product of waterproof and oil-proof agent in the textile field is still fluorine-containing acrylic emulsion. Although non-fluorine waterproof agents, such as paraffin type and silicone type waterproof agents, have appeared on the market in recent years, the performance of such products is still not comparable to that of fluorine-containing waterproof agents, and non-fluorine waterproof agents have almost no oil-proof performance. At present, the market share of non-fluorine is less than 10%. If the customer does not specify the use of non-fluorine waterproof agents, fluorine-containing waterproof agents are still the first choice for customers. At present, C8 type waterproof and oil-proof agent is the main fluorine waterproof agent, which is mainly due to the side chain of 8C fluorine-containing monomers can crystallize, resulting in better waterproof and oil-proof performance. Current research results show that the importance of determining surface performance is not the static contact angle, but the dynamic contact angle, especially the receding contact angle. Due to the crystallinity of the side chain of the 8-carbon monomer, its receding contact angle is significantly higher than that of short-chain fluorine monomers with 7 or less side chains. However, since the 8C fluorine-containing monomer will evolve into PFOA, PFOA has been proven to have the defects of strong bioaccumulation and difficulty in degradation.
[0003] Fiber products treated with water-repellents are widely used in daily clothing, outdoor sportswear, medical textiles, etc. As people's living standards improve, they are expected to further improve the waterproofness, oil resistance, and softness of these fiber products, especially the need to maintain these properties for a long time, that is, the washing durability requirements are getting higher and higher.
[0004] In order to solve the problem of durability after washing, Japanese Patent Application Laid-Open Nos. 2000-212549 and 2000-282016 disclose the effectiveness of specific crosslinking monomers.
[0005] In order to improve the washing durability, the patent document (CN106536622A) compounded a blocked isocyanate cross-linking agent in the waterproofing agent when treating the fabric to improve the washing durability.
[0006] Some patent documents also disclose the use of vinyl chloride and vinylidene chloride to improve the washing durability of water-repellents, which is also improved to a certain extent compared with water-repellents that do not use vinyl chloride and vinylidene chloride.
[0007] However, the above methods can only improve the washing durability to a certain extent. Conventional short-chain fluorinated monomers, such as C4, C6, etc., have certain gaps compared with C8 waterproofing agents in the early stage due to their own structural defects. Therefore, in terms of washing durability, they still cannot achieve the washing durability performance of conventional C8 waterproofing agents. Summary of the invention
[0008] 1. Technical issues to be solved In view of the shortcomings of the prior art, the present invention provides an environmentally friendly waterproof and oil-proof emulsion with excellent washing durability, as the existing conventional short-chain fluorinated monomers cannot reach the level of C8 waterproof agents. Although C6 or C4 fluorinated monomers are used, the washing durability can still achieve the same level as the conventional C8 waterproof agent.
[0009] (II) Technical solution To achieve the above object, the present invention provides the following technical solutions: An environmentally friendly waterproof and oil-proof emulsion with excellent washing durability, comprising, by mass fraction: Fluorinated copolymer 10-30%, Deionized water 50-70%, Emulsifier 1~10%, Cosolvent 1~10%.
[0010] Further: In terms of mass fraction, the fluorine-containing copolymer comprises: Fluorinated monomer 20-60%, Long chain alkyl acrylate 10-30%, Chlorine-containing monomer 1~20%, Cross-linking monomer 1~30%.
[0011] Preferably: the fluorine-containing monomer is composed of two fluorine-containing monomers, one of which has a melting point greater than 80°C and a content of 10-40% in the fluorine-containing copolymer; Another fluorine monomer has a glass transition temperature of less than 20°C and its content in the fluorine-containing copolymer is 10-20%.
[0012] Preferably, the side chain length of the long-chain alkyl acrylate is 12 to 30.
[0013] Preferably, the chlorine-containing monomer is vinyl chloride monomer or vinylidene chloride monomer.
[0014] Preferably, the cross-linking monomer is an acrylate monomer with two functional groups, a C=C compound and a reactive group compound.
[0015] Preferably, the crosslinking monomer is one or more of hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, epoxy (meth)acrylate, diacetone (meth)acrylamide, N-hydroxymethylacrylamide, 3-chloro-2-hydroxypropyl (meth)acrylate, and glycidyl (meth)acrylate.
[0016] Preferably, the emulsifier is composed of a cationic emulsifier and a nonionic emulsifier, wherein the cationic emulsifier accounts for 30-60% of the emulsifier, and the structural formula is R(CH 3 ) 3 N + X - , wherein R is a long-chain alkyl of 12-18, X is a halogen atom of chlorine or bromine; the nonionic emulsifier is a surfactant of alkyl polyoxyethylene ether structure, with the general formula of RO(CH 2 CH 2 O) n H, wherein R is a long-chain alkyl of 12-20, n is 3-50, and the proportion in the emulsifier is 40-70%.
[0017] Preferably, the co-solvent is a high-boiling alcohol solvent having a boiling point higher than 150° C., which is one or more of propylene glycol, dipropylene glycol, and tripropylene glycol.
[0018] On the other hand, the present invention also discloses a method for preparing an environmentally friendly waterproof and oil-proof emulsion with excellent washing durability, comprising the steps of: 1) The melting point T m Fluorine monomer, glass transition temperature T greater than 80°C g Fluorine-containing copolymer composed of fluorine monomer, long-chain alkyl acrylate, chlorine-containing monomer and cross-linking monomer less than 20°C; 2) Preheat the fluorinated copolymer obtained in step 1), deionized water, emulsifier and cosolvent in a 60°C water bath for 40 to 60 minutes, pre-disperse under mechanical stirring, and finally homogenize under a high-pressure homogenizer to obtain a metastable emulsion with a particle size of less than 150 nm, wherein the sum of the mass percentages of the fluorinated copolymer, deionized water, emulsifier and cosolvent used is 100%; 3) The emulsion obtained in step 2) is introduced into a closed high-pressure reactor with mechanical stirring, and the chlorine-containing monomer is pressed into it. When the temperature rises to 50-80°C, 0.1-0.5% of the chain transfer agent dodecyl mercaptan and 0.4-2.0% of the initiator are added to the copolymer monomer. The polymerization reaction time is 3-6 hours, and finally the temperature is cooled to room temperature and filtered to obtain a fluorine-containing polymer emulsion.
[0019] Preferably, the initiator is one or a combination of water-soluble azobisisobutylamidine hydrochloride, ammonium persulfate, potassium persulfate.
[0020] Preferably, the initiator may also be an azo or peroxide type oil-soluble initiator.
[0021] The copolymer emulsion obtained by the technical scheme of the present invention is translucent with blue light, the particle size of the polymer emulsion is in the range of 50 to 150 nm, and the molecular weight of the fluorine-containing polymer is in the range of 10,000 to 100,000.
[0022] (III) Beneficial effects The fluorine-containing emulsion with excellent washing durability obtained by the present invention introduces two or more different T g or T m Environmentally friendly fluorinated monomers, which produce the following effects: 1. The fluorinated monomers used in the present invention are C6 or C4 fluorinated monomers, and there are no C8 or above components with strong environmental accumulation; 2. T used in the present invention m The fluorinated monomers with a temperature greater than 80°C increase the advancing contact angle of the polymer, that is, the anti-reconstruction property of the polymer film. g The fluorinated monomer with a temperature lower than 20°C not only improves the film-forming property of the polymer film, but also increases the contact angle of the polymer film to the oil. g or T m The fluorinated monomer improves the contact angle to water and oil, the anti-reconstruction performance of the polymer film, and improves the softness of the film, and the softness of the film is conducive to improving the washing durability. DETAILED DESCRIPTION
[0023] The technical solutions in the embodiments of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.
[0024] The raw materials used in the examples and comparative examples are all commercially available industrial products and can be purchased through commercial channels.
[0025] Different T g and T m The fluorinated monomers are shown in Table 1.
[0026]
[0027] Among them, C6NSFA has two Tms, Tm=107℃ is the first transition temperature, and Tm=182℃ is the second transition temperature.
[0028] Example 1 Add the following components into a 500ml plastic beaker: C6NSFA 40g, C4FA 20g, octadecyl acrylate (C18A) 17g, N-hydroxymethyl acrylamide (NMA) 3g, nonionic emulsifier C 12 H 25 O(CH 2 CH2 O) 20 H 6g, cationic emulsifier C 18 H 37 N + (CH 3 ) 3 CL - 4g, tripropylene glycol 20g, deionized water 200g, then placed in 60 DEG C of water-baths and heated for 40 minutes, disperser dispersed 4 minutes, rotating speed 2000rpm / m, then placed in high pressure homogenizer homogenization 10 minutes, homogenization pressure 400kg, obtain stable oil-in-water type miniemulsion, average particle size is 150nm.Then the emulsion is poured into the autoclave equipped with agitator, after nitrogen replacement, vinyl chloride (VCM) 25 grams, then initiator azobisisobutylamidine hydrochloride 0.5g and dodecyl mercaptan 0.2g are added, water temperature rises to 75 DEG C simultaneously, after reaction 6 hours, obtain stable polymer aqueous dispersion.Tested by GC, monomer conversion is more than 99%; Calculated by F analysis, vinyl chloride monomer conversion is 80%.
[0029] Example 2 The C4FA in Example 1 was replaced by C6FA, and octadecyl acrylate was replaced by behenyl acrylate (C22A). The rest was the same as Example 1.
[0030] Example 3 The C6NSFA in Example 1 was replaced by C6SMFA, and octadecyl acrylate was replaced by behenyl acrylate. The rest was the same as in Example 1.
[0031] Example 4 The C6NSFA in Example 2 is replaced by C6SMFA, and the rest is the same as Example 1.
[0032] Example 5 The C6NSFA in Example 1 is replaced by C6SFA, and the rest is the same as Example 1.
[0033] Example 6 The amount of C4FA was adjusted from 20g to 10g and the amount of C6FA was adjusted to 10g. The rest was the same as in Example 1.
[0034] Comparative Example 1 The two fluorine monomers in Example 1 were replaced with C6FMA, and the rest were the same as Example 1.
[0035] Comparative Example 2 The two fluorine monomers in Example 1 are replaced with C4FMA, and the rest are the same as Example 1.
[0036] Comparative Example 3 The two fluorine monomers in Example 1 were replaced with C8FA, and the rest were the same as Example 1.
[0037] Comparative Example 4 The two fluorine monomers in Example 1 were replaced with a single fluorine monomer C6NSFA, and the rest was the same as Example 1.
[0038] The two fluorine monomers in Example 1 were replaced with a single fluorine monomer C6SFA, and the rest was the same as Example 1.
[0039] The amount of each monomer is shown in Table 2:
[0040] The tests were carried out on three kinds of fabrics (nylon, polyester and cotton) with a test concentration of 4.0%. The cross-linking agent was blocked isocyanate type BN-69 with a dosage of 1%. The test was carried out by dipping and rolling at 170°C for 2 minutes, and then the water and oil repellency was evaluated.
[0041] Water and oil repellent washing durability: According to the AATCC-35 washing method, wash repeatedly ten times and twenty times, and then evaluate the water and oil repellency (HL5, HL10, HL20). HL0 refers to the evaluation without washing.
[0042] Water repellency test: The test standard is AATCC-22. Using a water spray test device, 250ml of tap water is poured on the object to be tested within 25 seconds, the wetting state of the fabric is observed, and the water repellency is evaluated. The test results are as follows: 100 points: The surface is not wetted and water droplets do not adhere to it; 90 points: The surface is not wet, but there are small water droplets attached; 80 points: The surface is wet in the form of water droplets; 70 points: a considerable part of the surface is wetted; 50 points: The surface is almost completely wetted; 0 points: Both the front and back sides are moistened.
[0043] Oil repellency test: The test standard is AATCC-118 method: First, use the lowest numbered test liquid to carefully drop five drops of 0.05mL liquid on the sample. If there is no penetration and wetting within 30 seconds, then drop the test liquid with a higher number on the sample. The test is continued until the test liquid wets the sample below or around the drop within 30 seconds. The oil repellency level of the sample is represented by the highest numbered test liquid that cannot wet the sample within 30 seconds. The evaluation level is shown in the following table.
[0044] The oil-proof test liquid is shown in Table 3:
[0045] Hand feel test: Place the fabric to be tested in a constant temperature and humidity room at 25°C±2°C and 65%±2% for 24 hours, and then evaluate the softness using the following standards.
[0046] O: soft; △: average; ×: Hard.
[0047] The test results are shown in Table 4:
[0048] In summary, the use of two or more fluorine monomers with different Tg and Tm for polymerization is significantly better than the product obtained by polymerizing one conventional fluorine monomer in terms of washing durability and hand feel.
Claims
1. An environmentally friendly waterproof and oil-proof emulsion with excellent washing durability, characterized in that: According to the quality score, it includes: Fluorinated copolymer 10-30%, Deionized water 50-70%, Emulsifier 1~10%, Solvent 1-10%; The fluorine-containing copolymer contains a fluorine-containing monomer, which is composed of two fluorine-containing monomers, one of which has a melting point greater than 80°C and a content of 10 to 40% in the fluorine-containing copolymer; Another fluorine monomer has a glass transition temperature of less than 20°C and its content in the fluorine-containing copolymer is 10-20%.
2. The environmentally friendly waterproof and oil-proof emulsion with excellent washing durability according to claim 1, characterized in that: In terms of mass fraction, the fluorinated copolymer comprises: Fluorinated monomer 20-60%, Long chain alkyl acrylate 10-30%, Chlorine-containing monomer 1~20%, Cross-linking monomer 1~30%.
3. The environmentally friendly waterproof and oil-proof emulsion with excellent washing durability according to claim 2, characterized in that: The side chain length of the long-chain alkyl acrylate is 12 to 30.
4. The environmentally friendly waterproof and oil-proof emulsion with excellent washing durability according to claim 2, characterized in that: The chlorine-containing monomer is vinyl chloride monomer or vinylidene chloride monomer.
5. The environmentally friendly waterproof and oil-proof emulsion with excellent washing durability according to claim 2, characterized in that: The cross-linking monomer is an acrylate monomer with two functional groups, a C=C compound and a compound with a reactive group.
6. The environmentally friendly water-proof and oil-proof emulsion with excellent washing durability according to claim 5, characterized in that: The crosslinking monomer is one or more of hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, epoxy (meth)acrylate, diacetone (meth)acrylamide, N-hydroxymethylacrylamide, 3-chloro-2-hydroxypropyl (meth)acrylate, and glycidyl (meth)acrylate.
7. The environmentally friendly waterproof and oil-proof emulsion with excellent washing durability according to claim 1, characterized in that: The emulsifier is composed of a cationic emulsifier and a nonionic emulsifier, wherein the cationic emulsifier accounts for 30-60% of the emulsifier and has a structural formula of R(CH3)3N + X - , wherein R is a long-chain alkyl of 12-18, X is a halogen atom of chlorine or bromine; the nonionic emulsifier is a surfactant of alkyl polyoxyethylene ether structure, and the general formula is RO(CH2CH2O) n H, wherein R is a long-chain alkyl of 12-20, n is 3-50, and the proportion in the emulsifier is 40-70%.
8. The environmentally friendly waterproof and oil-proof emulsion with excellent washing durability according to claim 1, characterized in that: The co-solvent is a high-boiling alcohol solvent with a boiling point higher than 150° C., which is one or more of propylene glycol, dipropylene glycol, and tripropylene glycol.
9. A method for preparing an environmentally friendly waterproof and oil-proof emulsion having excellent washing durability according to any one of claims 1 to 8, characterized in that: Includes steps: 1) The melting point T m Fluorine monomer, glass transition temperature T greater than 80°C g Fluorine-containing copolymer composed of fluorine monomer, long-chain alkyl acrylate, chlorine-containing monomer and cross-linking monomer less than 20°C; 2) Preheat the fluorinated copolymer obtained in step 1), deionized water, emulsifier and cosolvent in a 60°C water bath for 40 to 60 minutes, pre-disperse under mechanical stirring, and finally homogenize under a high-pressure homogenizer to obtain a metastable emulsion with a particle size of less than 150 nm, wherein the sum of the mass percentages of the fluorinated copolymer, deionized water, emulsifier and cosolvent used is 100%; 3) The emulsion obtained in step 2) is introduced into a closed high-pressure reactor with mechanical stirring, and the chlorine-containing monomer is pressed into it. When the temperature rises to 50-80°C, 0.1-0.5% of the chain transfer agent dodecyl mercaptan and 0.4-2.0% of the initiator are added to the copolymer monomer. The polymerization reaction time is 3-6 hours, and finally the temperature is cooled to room temperature and filtered to obtain a fluorine-containing polymer emulsion.
10. The method for preparing an environmentally friendly waterproof and oil-proof emulsion with excellent washing durability according to claim 9, characterized in that: The initiator is one or a combination of water-soluble azobisisobutylamidine hydrochloride, ammonium persulfate and potassium persulfate.
11. The method for preparing an environmentally friendly waterproof and oil-proof emulsion with excellent washing durability according to claim 9, characterized in that: The initiator is an oil-soluble initiator of azo type or peroxide type.
Citation Information
Patent Citations
Composition comprising mixtures of polyacryates with fluorine-containing polyacrylates
CN106536622A
Water-repellent and oil-repellent composition and its production
JP2000212549A
Water-repelling and oil-repelling agent composition
JP2000282016A
Photosensitive resin composition, photosensitive transfer material, pixel barrier and method for forming the same, substrate with pixel barrier, color filter and method for producing the same, and dis
CN101535357A
Low-temperature crosslinking fluorine-containing nuclear shell type water-repellent and oil-repellent finishing agent emulsion and preparation method thereof
CN103435745A